Upaya Meminimalkan Dampak Eksploitasi Udang Windu (Penaeus monodon, Fabricus 1798) dengan Penentuan Ukuran Tangkap di Perairan Tarakan, Kalimantan Utara - Andri Warsa; Amran Ronny Syam; Duranta Diandria Kembaren (Jurnal Airaha, 2019)
The Tiger prawn (Penaeus monodon, Fabricus 1798) was dominantly captured at Tarakan waters, North Borneo. The captured activity in this area was done annually and shown over the exploitation rate. Its need an effort to minimizing exploitation impact for sustainability management. Legal size determination is one effort for resources management. The aim of this paper was to the determination of legal size as an effort for sustainability management of tiger prawn at Tarakan Waters, North Borneo. Population parameters of tiger prawn were used in this paper from the article was published in 2013 and 2018. Tiger Prawn samples collected from fishermen captured was landed at Lingkas Ujung (2012) and Selimit Pantai (2016) landing site, Tarakan, North Borneo. Result of the research shown length at first captured (Lc) of tiger prawn is 33.6 mm and smaller than a length at first mature (Lm) is 40.7 mm. The tiger prawn size (Lc_opt) for exploitation 47-50 mm. it was bigger than Lm and give optimal economic value.